EFFECT OF CROP ROTATIONS, WEED CONTROL METHODS AND TYPE OF SOWING/PLANTING BED ON PRODUCTION, ECONOMICS AND NUTRIENT REMOVAL IN POTATO BASED CROPPING SYSTEMS - Singh, Shiv Pratap; Sharma, Sanjay Kumar; Sadawarti, Murlidhar J; Dua, Vijay Kumar; Rawal, Sanjay; Kumar, Manoj (Potato Journal, 2021)
World has an oversupply of mouths to feed and an under supply of arable land and useable irrigation water. Balancing productivity, profitability, and environmental health is a key challenge for agricultural sustainability. A field experiment was conducted during 2014-15 and 2015-16 at the experimental site to identify suitable cropping system, appropriate weed management practice and type of planting method. Results indicated that higher grain yield was recorded with pearl millet (2520 kg/ha) compared to soybean (960 kg/ha). Significantly higher yield was recorded with normal type bed (1873 kg/ha) compared to raised bed (1622 kg/ha). Highest grain yield (2039 kg/ha) was recorded with herbicide + hoeing treatment, which was significantly higher than herbicide and weedy check treatments. Lowest grain yield (1453 kg/ ha) was recorded with weedy control. Interaction of pearl millet √ herbicide + hoeing recorded significantly higher grain yield. Cropping system and type of bed did not show any significant effect on yield of small, medium, large and total tuber yields. Highest small (3.3 t/ha), large size (15.4 t/ha) and total tuber yields (27.4 t/ha) were recorded with weedy check control. Soybean based cropping system √ raised bed type of planting recorded highest small size tubers (3.4 t/ha). Soybean based cropping system √ ridge-furrow planting method recorded highest large size tubers (15.2 t/ha). Potato equivalent yield was 32.4 t/ha under soybean-potato system though it was statistically similar to pearl millet – potato sequence. Net return was Rs. 127.9 thousand/ha in pearl millet - potato cropping system compared to Rs. 82.6 thousand/ha in soybean - potato cropping system although both were statistically same. Similar trend was recorded with B:C ratio which was 2.1 in weedy check compared to 1.9 in herbicide + hoeing. Values were statistically same due to cropping system, type of planting/sowing and weed control methods. N, P and K uptakes were statistically same in both the cropping systems. Highest N uptake (246.6 kg/ha/year) was recorded with raised bed planting system compared to normal bed. Similarly weedy check control recorded highest uptake (253.5 kg N/ha) among weed management practices and raised bed √ weedy check control interaction recorded highest value (278.6 kg N/ha). Highest P uptake (47.6 kg/ha/year) was recorded with normal bed planting, weedy check control (43.6 kg P/ha) and interaction of pearl millet – potato cropping system √ normal type of bed (58.3 kg P/ha/year) and pearl millet – potato cropping system √ herbicide weed control method (50.0). Uptake of K was neither affected by cropping systems nor by type of bed systems. Highest K uptake (203.8 kg/ha) was recorded with weedy check control. Hence, it is concluded that pearl millet – potato cropping system, escaping weed control under least weed pressure situation during rabi season and herbicide weed control and normal planting methods may be followed. Integrated weed control was not suitable for potato but suitable for kharif crops. Cropping systems did not show any significant effect on soil OC. Highest OC (0.33%) was recorded with herbicide applied treatment which was significantly higher than herbicide + hoeing but at par with weedy check.